A Close and Supportive Interparental Bond During Pregnancy Predicts Greater Decline in Sexual Activity From Pregnancy to Postpartum: Applying an Evolutionary Perspective - Lorenz, Tierney K.; Ramsdell, Erin L.; Brock, Rebecca L. (Frontiers in Psychology, 2020)
A common topic for advice given to parents after childbirth -both from relationship experts and popular media -is how to "bounce back" to one's pre-pregnancy sexuality, with warnings that postpartum declines in sexual frequency will take a serious toll on one's relationship. However, these admonishments may not accurately reflect the ways in which the unique reproductive context of pregnancy and the postpartum transition alter associations between sexual frequency and relationship quality. Evolutionary perspectives on reproductive strategies would suggest that in the postpartum context, decreased sexual activity would help target parental investment in the current offspring (rather than creating new offspring); however, if the parental relationship is lacking in intimacy and support, continued sexual activity may help seal the cracks in the bond. We tested this theory in a longitudinal dyadic study of changes in relationship quality and sexual frequency from pregnancy to six months postpartum among heterosexual couples. We found that across three different measures of relationship quality taken from interviews and behavioral observation of couple interactions, higher relationship quality (i.e., greater support, intimacy, and responsiveness) predicted greater decline in sexual frequency whereas sexual frequency remained relatively stable in lower quality relationships. These findings suggest that, during the postpartum transition, decreased sexual frequency may not be a reliable signal of poor relationship quality.